Understanding the structure and function of the immunological synapse. - Dustin, M; Chakraborty, A; Shaw, A (2010)
The immunological synapse has been an area of very active scientific interest over the last decade. Surprisingly, much about the synapse remains unknown or is controversial. Here we review some of these current issues in the field: how the synapse is defined, its potential role in T-cell function, and our current understanding about how the synapse is formed.